2005
DOI: 10.1091/mbc.e05-04-0295
|View full text |Cite
|
Sign up to set email alerts
|

Na/K-ATPase Tethers Phospholipase C and IP3 Receptor into a Calcium-regulatory Complex

Abstract: We have shown that the caveolar Na/K-ATPase transmits ouabain signals via multiple signalplexes. To obtain the information on the composition of such complexes, we separated the Na/K-ATPase from the outer medulla of rat kidney into two different fractions by detergent treatment and density gradient centrifugation. Analysis of the light fraction indicated that both PLC-␥1 and IP3 receptors (isoforms 2 and 3, IP3R2 and IP3R3) were coenriched with the Na/K-ATPase, caveolin-1 and Src. GST pulldown assays revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
211
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 201 publications
(218 citation statements)
references
References 48 publications
(89 reference statements)
6
211
0
1
Order By: Relevance
“…These studies demonstrated that ouabain activated Src by stimulating the phosphorylation of Tyr-418 and that the activation of Src was required for ouabaininduced transactivation of EGF receptors and many other protein kinase and lipase cascades (4,8,31). Subsequently, we and others have found that the ␣1 Na/K-ATPase and Src co-localized in the plasma membrane and that they could be coimmunoprecipitated from cell lysates.…”
Section: Discussionmentioning
confidence: 88%
“…These studies demonstrated that ouabain activated Src by stimulating the phosphorylation of Tyr-418 and that the activation of Src was required for ouabaininduced transactivation of EGF receptors and many other protein kinase and lipase cascades (4,8,31). Subsequently, we and others have found that the ␣1 Na/K-ATPase and Src co-localized in the plasma membrane and that they could be coimmunoprecipitated from cell lysates.…”
Section: Discussionmentioning
confidence: 88%
“…Previous reports indicate that Na,K-ATPase signal transduction stimulates proliferation in smooth muscle cells (11) and apoptosis in prostate cancer cells (12). Ouabain, an endogenously synthesized hormone (13,14), is Na,K-ATPase's ligand and forms a hormone-receptor complex capable of inducing mitogen-activated protein (MAP) kinase phosphorylation (15,16) and intracellular Ca 2ϩ signaling (17)(18)(19).…”
mentioning
confidence: 99%
“…Studies from many laboratories have now established that the binding of ouabain to this enzyme not only inhibits the ATPase activity but also stimulates protein tyrosine kinases such as Src (4,5). The activated Src in turn transactivates epidermal growth factor receptor, resulting in the assembly and activation of multiple signaling cascades such as the ERK1/2 2 and phospholipase C-␥/ protein kinase C pathways (5,6).…”
mentioning
confidence: 99%